Role of carbohydrate-active enzymes in brown planthopper virulence and adaptability - Liu, Fang; Xiao, Jing; Wang, Xin-Feng; Wang, Ya-Xuan; Yang, Hou-Hong; Cai, Yu-Biao; Lai, Feng-Xiang; Fu, Qiang; Wan, Pin-Jun (Frontiers in Plant Science, 2025)
IntroductionHerbivorous insects, including the brown planthopper (BPH), Nilaparvata lugens, are among the most damaging pests to agricultural crops worldwide, particularly rice. These insects employ a variety of strategies to overcome plant defenses, including the secretion of carbohydrate-active enzymes (CAZymes) that degrade plant cell walls. While CAZymes are well-studied in other insect species, their role in BPH virulence remains largely unexplored. MethodsThis study aims to address this gap by analyzing CAZymes in 182 insect genomes, followed by a detailed genomic and transcriptomic analysis of BPH.ResultsWe identified 644 CAZymes in BPH, including enzymes related to plant cell wall degradation. Through quantitative real-time PCR (RT-qPCR) and subcellular localization experiments, we found that 5 candidate genes exhibited increased expression during feeding on the susceptible rice variety TN1, a well-characterized variety highly susceptible to BPH and these genes were localized to the plasma membrane. Our results suggest that BPH CAZymes play a critical role in the insect's ability to feed and damage rice plants.DiscussionThis study provides valuable insights into the molecular mechanisms underlying insect adaptation and virulence in the co-evolutionary process between plants and herbivorous insects. By exploring the function of pest-related genes in the BPH and examining their differential responses in rice varieties with varying resistance to BPH, we aim to contribute to the development of targeted pest management strategies.